L-FABP and I-FABP expression in newborn rats changes inversely in the model of necrotizing enterocolitis - Mitidiero,Luís Felipe Tsuyoshi (2014)
PURPOSE: To determine the expression of hepatic L-FABP and intestinal I-FABP in an experimental model of necrotizing enterocolitis (NEC) in neonatal rats.METHODS: Newborn Sprague-Dawley rats were divided into four groups: Control (C1) - exclusive breastfeeding at the first and sixth procedures (C6), NEC1 - fed formula milk and submitted to hypoxia and hypothermia at the first and sixth procedures (NEC6). The newborn pups were fed twice a day for three days, for a total of six procedures. Samples were collected for morphometric evaluation (body weight, liver weight, liver weight/body weight ratio, intestinal weight and intestinal/body weight ratio) and for immunohistochemical and Western blotting analysis. The values obtained were analyzed statistically, with the level of significance set at p<0.05.RESULTS:Morphometric measurements showed reduction of body and liver weights in the NEC group (p<0.05). Both immunohistochemistry and western blotting revealed that L-FABP expression in the liver was decreased and I-FABP expression in the ileum was increased in the NEC group (p<0.05).CONCLUSION: L-FABP and I-FABP expression changed inversely in the rat NEC model. These findings can contribute to a better diagnosis of NEC in human newborns.